Market Failure, Government Failure, Leadership and Public Policy: with the introduction of Bob Jessop - Dollery, Brian F.; Wallis, Joe L. (Journal of Public Governance, 2009)
The economic rationale for government intervention in a market economy has traditionally been provided by the theory of market failure. This article reviews the market failure paradigm in the light of the more recent literature on government failure. One implication of the theory of government failure is that the contractualist approach to public service reform is the best method of improving public sector productivity. However, we argue that this view overlooks the potentially crucial role of leadership in public agencies and the ways in which transformational leadership can stimulate efficiency. We argue that communitarian conceptions of leadership can be incorporated into conventional economic approaches, and that this can have significant implications for public policy formulation.